Factores que intevienen en el bajo rendimiento acádemico de los estudiantes del tercero de bachillerato de la especialidad de electromecánica automotriz del Instituto Técnico Superior Salesiano de la ciudad de Cuenca - Espinoza Ambrosi, Mirian Marcela (2008)
In the present I investigation, we have accomplished a statistical analysis based in opinion polls applied to the students and the Technical Superior Salesian Institute's teachers of Automotive Electromecanica's specialty, to determine the causes of the low academic performance in the technical area, for it we have set some objectives that are headed toward this aim. Considering always to the student like a center of the educational process, and basing us on the PROSIEC's general guidelines. The results of investigation appear result in the following points: The low performance is due three fundamental factors, first at all, the vocational guidance carried in a superficial form; secondly, the methodology applied by the teachers of the technical area is not the suitable; And finally the deficient implementation of tools and didactic material of the specialty, as well as the deficiency of a propitious environment for workshops. At the end of the investigation, we have formulated some general guidelines with respect to the three above-mentioned aspects, the same that they will be useful for improving the academic performance of the students of the specialty under consideration, and in general for the better educational task inside the Salesian Institution.